2022
DOI: 10.1155/2022/7377877
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Dysfunction Could Be a Cause of Heart Failure with Preserved Ejection Fraction Development in a Rat Model

Abstract: 50% of patients with heart failure have a preserved ejection fraction (HFpEF). Numerous studies have investigated the pathophysiological mechanisms of HFpEF and have shown that endothelial dysfunction plays an important role in HFpEF. Yet no studies answered whether endothelial dysfunction could be the cause or is the consequence of HFpEF. Recently, we have shown that the endothelial overexpression of human β3-adrenoreceptor (Tgβ3) in rats leads to the slow development of diastolic dysfunction over ageing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Another prevailing theory is that obesity-associated HFpEF is driven by a comorbidity-induced systemic proinflammatory state [ 39 41 ]. For example, the microRNA miR-181c is differentially expressed in patients with diabetes and comorbid HFpEF, and overexpression of miR-181c has been associated with proinflammatory conditions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another prevailing theory is that obesity-associated HFpEF is driven by a comorbidity-induced systemic proinflammatory state [ 39 41 ]. For example, the microRNA miR-181c is differentially expressed in patients with diabetes and comorbid HFpEF, and overexpression of miR-181c has been associated with proinflammatory conditions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained by measuring the overall peak amplitude of the generated spectra and normalizing it to the sample's dry weight in arbitrary units (A.U.) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Second, GHRH-A restored several markers of myocardial inflammation to normal. Endothelial dysfunction has been proposed to link chronic systemic inflammation with myocardial dysfunction and remodeling in HF (41)(42)(43). Schiattarella et al (23) suggested a role of iNOS activation and metabolic inflammation in HFpEF pathogenesis.…”
Section: Effect Of Ghrh-agonist Mr-356 On Inflammationmentioning
confidence: 99%